2011
DOI: 10.1152/ajpheart.00411.2010
|View full text |Cite
|
Sign up to set email alerts
|

Increased myocardial stiffness with maintenance of length-dependent calcium activation by female sex hormones in diabetic rats

Abstract: Bupha-Intr T, Oo YW, Wattanapermpool J. Increased myocardial stiffness with maintenance of length-dependent calcium activation by female sex hormones in diabetic rats. Am J Physiol Heart Circ Physiol 300: H1661-H1668, 2011. First published February 18, 2011 doi:10.1152/ajpheart.00411.2010.-A decrease in peak early diastolic filling velocity in postmenopausal women implies a sex hormonerelated diastolic dysfunction. The regulatory effect of female sex hormones on cardiac distensibility therefore was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 46 publications
(61 reference statements)
2
28
0
Order By: Relevance
“…This finding is consistent with an earlier report demonstrating unchanged passive stiffness in OVX animals (56). No differences were found in the phosphorylation of myofilament proteins between the control and control-S groups.…”
Section: Discussionsupporting
confidence: 94%
“…This finding is consistent with an earlier report demonstrating unchanged passive stiffness in OVX animals (56). No differences were found in the phosphorylation of myofilament proteins between the control and control-S groups.…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with previous studies [20, 21], the present experiments demonstrated that isometric force and passive stiffness values measured in pCa 9.0 solutions with minimal free Ca 2+ did not differ between the CTRL and STZ groups at physiological sarcomere lengths (p>0.05 for STZ, sex and interaction, Linear Mixed Model, Table 3). SDS-VAGE gels [17] did however show a small but statistically significant reduction in the proportion of titin found as the ‘stiff’ N2B isoform (molecular weight ~2.97 MDa) in the STZ samples (2 way ANOVA, p<0.008, STZ).…”
Section: Resultssupporting
confidence: 92%
“…The percentage of titin expressed as the larger N2BA isoform, N2BA-A1 (~3.39 MDa) was increased in the STZ animals while the relative content of the smaller N2BA-A2 isoform (~3.22 MDa) was decreased (Table 5) [22]. Myocardial collagen content was not measured in this work but others [21] have shown that it could be increased by streptozotocin injection at 6 weeks.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, as oxidative stress has been shown to reduce myofilament Ca 2+ sensitivity in the heart [59], it is possible that an increase in production of ROS leads to the decrease in myofilament Ca 2+ sensitivity observed in our study. On the other hand, previous studies have reported that short-term (10 weeks) OVX increases myofilament Ca 2+ sensitivity [60], so prolonged ovarian estrogen withdrawal may be required to desensitize myofilaments in the aging female heart. ROS also reduces SERCA2 activity, which is not compatible with the faster time courses of contraction and Ca 2+ transients observed in our study [58,61].…”
Section: Discussionmentioning
confidence: 99%